Preservasi Koleksi Perpustakaan dari Sudut Pandang Islam - Dwi Arsita Mursalim; Tasbih Tasbih; Subehan Khalik (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2026)
This study aims to understand the Islamic perspective on library collection preservation. This approach is not merely about library management but also combines modern preservation practices with Islamic principles, such as the obligation to preserve the heritage of knowledge for future generations. The goal is to demonstrate that preservation is not merely an administrative task but also a moral act of worship that aligns with Islamic teachings on preserving the authenticity of knowledge, as emphasized in the hadith regarding remembering, conveying, and recording knowledge. This article applies a qualitative research method through descriptive analysis. Data collection was conducted by researching and studying relevant literature on library collection preservation from an Islamic perspective. A literature review is a written summary of articles, books, and other documents that explain theories and information, both past and present, regarding the topic and literature. Therefore, the approach taken in this work is a literature study with an emphasis on analyzing, summarizing, and collecting literature related to library collection preservation. The results of this study indicate that from an Islamic perspective, preservation of collections is a responsibility to protect the heritage of knowledge for future generations, in accordance with teachings that emphasize the need to maintain sustainability and not damage the environment.